2020
DOI: 10.2147/ijn.s257230
|View full text |Cite
|
Sign up to set email alerts
|

<p>Oxygen Functional Groups on MWCNT Surface as Critical Factor Boosting T2 Relaxation Rate of Water Protons: Towards Improved CNT-Based Contrast Agents</p>

Abstract: Purpose: Salicyl (Sal)-among other oxygen functionalities-multi-walled carbon nanotubes (MWCNTs) and their nanohybrids are investigated as promising contrast agents (CA) in magnetic resonance imaging (MRI) or drug delivery platforms, due to their unique properties. The preliminary results and the literature reports were the motivation to endow high r 2 relaxivities, excellent dispersibility in water, and biocompatibility to superparamagnetic MWCNTs nanohybrids. It was hypothesized that these goals could be ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Indeed, the maximum occurrence in ZFC curves can be associated with the blocking process of some Fe-complexes as nanoparticle catalyst residues. The observed M(T) variations are relatively consistent with previously published results [ 23 , 34 ]. Jamrozik et al [ 34 ] revealed that the M(T) dependence at a lower temperature for all studied nanotubes is different than expected for pure cementite, suggesting the influence of additional iron-based species, which lead to a slight increase in magnetization with decreasing temperature.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Indeed, the maximum occurrence in ZFC curves can be associated with the blocking process of some Fe-complexes as nanoparticle catalyst residues. The observed M(T) variations are relatively consistent with previously published results [ 23 , 34 ]. Jamrozik et al [ 34 ] revealed that the M(T) dependence at a lower temperature for all studied nanotubes is different than expected for pure cementite, suggesting the influence of additional iron-based species, which lead to a slight increase in magnetization with decreasing temperature.…”
Section: Resultssupporting
confidence: 92%
“…As the authors claim, the magnetization results demonstrate a predominant amount of iron in the ferromagnetically ordered (or in the form of superparamagnetic particles) cementite phase. Smaller magnetization values for MWCNTs samples than that of bulk Fe 3 C can also be caused by some additional diamagnetic elements such as oxygen present in the samples [ 23 , 34 ]. Indeed, as shown by XRD and XPS analysis, the diamagnetic elements are observed in all studied samples, but their relative contribution is reduced after calcination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further increase in the concentration of nitrogen atoms in CNTs makes no sense since this leads to a critical decrease in the length of nanotubes with a slight change in the electronic characteristics [26]. The presence of oxygen in the XPS spectra of all synthesized nanotubes is due to its adsorption from the atmosphere, as well as the presence of chemically bonded functional groups of various types, which are always present on the surface [27]. The high-energy C5 component of the spectrum corresponds to the state of carbon atoms in the composition of -COOH groups [25].…”
Section: Resultsmentioning
confidence: 99%
“…Its signal intensity is related to factors such as proton density, longitudinal (T 1 ) and transversal (T 2 ) relaxivity times and the cellular microenvironment and can be enhanced by the use of CAs. [131][132][133] Common Gd complexes, such as Magnevist, are widely used as CAs due to their long electron spin relaxation time but have disadvantages such as short cycle time in the body, low longitudinal relaxation (R 1 ) and single function. Using plant polyphenols as organic ligands to synthesize Gd/ Fe-bimetallic-phenolic coordination polymer NPs can effectively enhance the R 1 , and the molar ratio of R 1 to Gd/Fe is positively correlated.…”
Section: Medical Imagingmentioning
confidence: 99%